Mechanical Design of Slug Catcher - Ayende; Arsyad, Mohammad Zafrullah; Widiyanto, Totok (Politeknik Energi dan Mineral Akamigas, 2021)
In the upstream oil and gas industry Slug Catcher is a separator to separate heavy liquid hydrocarbons and the gaseous lighter fraction. Slug Catcher is a cylindrical pressure vessel which has a horizontal orientation designed with an internal pressure of 84.37 kg/cm2 , 73,89 Â°C temperature, 3 mm corrosion allowance, 3,500 mm length, and 1,750 mm diameter. This paper aims to design a Slug Catcher from a mechanical side that is safe and able to withstand the stress caused by internal pressure. General design which includes calculation of thickness of shell, heads, and nozzles, maximum allowable working pressure (MAWP), and minimum design metal temperature (MDMT) using ASME BPVC Section VIII Division 1. Based on the results obtained the nominal shell thickness is 60 mm, head minimum thickness 58 mm, material specification for shell and head is SA 516 Gr 70. In general, the selected material use low carbon steel; flange rating class 600; vesselâ€™s Maximum Allowable Working Pressure is 87.60 kg/cm2 ; hydrostatic test pressure is 113 kg/cm2 .